Comparison of Hydrocarbon Volumetric Calculation between Cell-Based Model and Numerical Integration - Oktaviani, Vania; Saroji, Sudarmaji; Trisna, Muhammad Destrayuda (POSITRON, 2024)
Volume estimation for hydrocarbon reserves is a challenging yet pivotal task in engineering for exploration and production. Advances in technology now enable us to compute volume integration using programming computation. Various approaches using numerical integration, including the trapezoidal, pyramidal, and Simpson's rule, along with cell-based models as comparative methods can be used for the calculation of hydrocarbon volume. In this study, original oil in place (OOIP) is employed to determine reserve oil volume.   The OOIP values obtained are 8.55 million m3 through cell-based calculations, 8.63 million m3 via the trapezoidal approach, 8.58 million m3 using the pyramidal method, and 8.57 million m3 with Simpson's 3/8 rule. The relative error ratio percentages between the cell-based model as the reference value and the numerical integration calculations as the measured values are 0.93% for the trapezoidal method, 0.35% for the pyramidal method, and 0.23% for Simpson's 3/8 rule. Simpson's 3/8 rule demonstrates the closest mathematical result to the cell-based model. Within this margin of error, the methodologies have been demonstrated to proficiently compute hydrocarbon reserves from real data through simplified and abbreviated processes.